Prevalence Of Skin Manifestations In Patients With Polycystic Ovarian Syndrome: p - Naveed, Tehseen; Kiyani, Asma Afzal; Kausar, Sameena; Naheed, Aqsa; Khan, Dawood; Malik, Sakina Sadiq (Journal of Rawalpindi Medical College, 2024)
Objective: This study aimed to determine the prevalence of cutaneous manifestations in PCOS patients. Method: This cross-sectional study was conducted in the dermatology department, Combined Military Hospital, Peshawar, from 1st January 2021 to 30th June 2021. After obtaining ethical approval from the hospital’s ethical and research committee, a total of 50 patients aged 15 to 45 years were included in the study fulfilling the inclusion criteria. Written informed consent was taken from each patient. All patients underwent general physical, systemic and dermatological examination. Venous blood sampling was done after overnight fasting for hormonal assays (TSH, LH, FSH, prolactin and testosterone), glucose, and lipid levels. An ultrasound scan was done for the detection of ovarian cysts. Results: Mean age was 26.96 years ± 5.42 SD. The mean BMI was 26.04 Kg/m2 ± 5.10 SD. Mean FSH and LH levels were 6.86 IU/L ± 5.41 SD and 12.11 IU/L ± 8.75 SD respectively. Among them, 88% were married, 36% had menstrual irregularities and 72% had infertility. Hirsutism, acne, acanthosis nigricans, and androgenic alopecia were noted in 72%, 54%, 42%, and 20% of the patients respectively. Conclusion: Cutaneous manifestations can play an important role in the diagnosis of PCOS and also contribute an important portion of the symptoms experienced by patients suffering from PCOS. Keywords: PCOS, Skin manifestations, Hyperandrogenism, Hirsutism, Acne.